Games Online dan Katarsis Virtual (Studi Kasus dengan Analisis Psikoanalisis Freud pada Kecenderungan Permainan Game Interaktif Point Blank dan Second Life) - Keken Frita Vanri; Benni Yusriza Hasbiyalloh (Ultimacomm: Jurnal Ilmu Komunikasi, 2011)
Interactivity, digitality, and virtuality are three important aspects of Internet technology, among others. Thanks to its break-through characteristics, internet brings many changes into the lives of people. Due to its accessible features and loads of information, many people’s needs on information, entertainment and social interaction are necessarily answered. One of the most interesting and widely developed features on internet is online game. Online game promises its users the ability to connect with other fellow users in real time. This paper intends to view online game as a second reality, different with the real world we live in. By employing psychoanalysis theory initiated and developed by Sigmund Freud, this paper sees online game as a playing field for human Id (Freudian biological desire), constantly repressed in real world due to its persisting conflict with ego and super ego. Online game commonly perceived as “unreal virtual sphere” facilitates its users to freely conduct certain actions which, in normal and real life, are forbidden, such as killing and raping. Therefore, online game could be perceived as catharsis, or outlet for bestial desire of human being. The hypotheses needs to be proven in this paper is whether sexual and violent character of online game really possess catharsis function to release the biological desire of the users, or, the other way around, namely, repressing the Id. The methodology used in this paper is case study with both observation as well as literature study relevant with online game in question. The authors attempt to observe directly and also conduct interview with ten children in five different internet shop (warnet). The theoretical paradigm used is twofold, namely, catharsis theory and Freudian psychoanalysis. To support the main paradigm used, the authors also use media dependency theory proposed by DeFleur, including, but not limited to, arousal and aggressive cues. Keywords : Game online, katarsis, psikoanalisis